Selbstreparaturen in der schriftlichen Interaktion Eine kontrastive Analyse deutscher und russischer Kurznachrichtenkommunikation - Mostovaia, Irina (Empirische Linguistik / Empirical Linguistics, 2021)
This empirical study examines self-initiated and other-initiated self-repairs in German and Russian SMS communication by applying methods from conversation analysis and interactional linguistics. It describes the sequential organization and functions of self-repairs in the analyzed data from the two languages and contrasts them with each other.